Spinal cord spectroscopy and diffusion-based tractography to assess acute disability in multiple sclerosis - Ciccarelli, O; Wheeler-Kingshott, C A; McLean, M A; Cercignani, M; Wimpey, K; Miller, D H; Thompson, A J (Brain (London, England : 1878), 2007)
There is a need to assess spinal cord involvement in multiple sclerosis with new imaging techniques in order to understand better the underlying pathology. We aimed to evaluate whether quantitative MRI measures, obtained using single-voxel (1)H-MR spectroscopy of the cervical cord and diffusion-based tractography of the major spinal cord pathways, in patients with a cervical cord relapse, differed from controls and correlated with acute disability. Fourteen patients at the onset of a cervical cord relapse with at least one lesion between C1 and C3 were imaged on a 1.5 T scanner and clinically assessed on the Expanded Disability Status Scale (EDSS), 9-hole peg test (HPT) and timed 25-foot walk test. Thirteen age- and gender-matched control subjects were also scanned. Metabolite concentrations, including total N-acetyl-aspartate (tNAA), choline-containing compounds (Cho), creatine plus phosphocreatine (Cr) and myo-Inositol (m-Ins), were quantified at C1-C3. Probabilistic tractography was performed at C1-C3 to track the lateral cortico-spinal tracts in the lateral columns, the anterior cortico-spinal tracts and the anterior spino-thalamic fasciculi in the anterior columns, and the bilateral fasciculus gracilis and cuneatus in the posterior columns. Diffusion- and tractography-derived measures of these tracts, including fractional anisotropy and voxel-based connectivity, which reflect fibre integrity, were obtained. These MRI measures were compared between patients and controls using the Mann-Whitney test. Univariate correlations between MRI measures and disability were assessed using the Spearman's rho correlation coefficient. Multiple regression analyses were performed to investigate which MRI measures independently correlated with the clinical scores, adjusting also for cross-sectional cord area, age and gender. Patients showed lower tNAA of the cervical cord, lower connectivity and lower fractional anisotropy of the lateral cortico-spinal tracts and posterior tracts, than controls. In patients, there were significant correlations between: (i) EDSS and m-Ins, Cho, Cr and radial diffusivity of the lateral cortico-spinal tracts; (ii) HPT and Cr, radial diffusivity of the lateral cortico-spinal tracts, connectivity and fractional anisotropy of the posterior tracts, and connectivity of the anterior tracts. M-Ins was independently associated with the EDSS, while Cr, tNAA and connectivity of the posterior tracts were independently associated with the HPT. MR spectroscopy and diffusion-based tractography of the cervical cord provide measures that are sensitive to the tissue damage occurring in this area in patients with a cervical cord relapse. These measures were found to correlate with acute disability. Our findings suggest that it would be worthwhile performing longitudinal studies and extending these novel techniques to other neurological diseases affecting the spinal cord.